A system dynamics model to analyze future electricity supply and demand in Iran under alternative pricing policies. (April 2021) - Dehghan, Hamed; Amin-Naseri, Mohammad Reza; Nahavandi, Nasim
Abstract: Ensuring sustainable electricity supply is a key issue facing decision-makers. Due to its impact on system reliability, balancing supply and demand is essential. Electricity subsidy policies in many countries have led to high consumption and low power plant efficiency, and may cause an imbalance in the future. This research analyzes different electricity subsystems using system dynamics to investigate how and when low energy prices lead to an unstable situation. Simulation results using Iran's data show demand surpasses supply with a continuation of current trends. However, when the prices increase 90%, demand is met, and subsidy decreases by about 20%. Highlights: A system dynamics model of electricity supply and demand is presented. The behavior of key variables in four subsystems is simulated under price policies. The results show that power supply fails to meet demand fully with current trend. In case of 90% rise in power and gas prices, demand is wholly met in all scenarios. In case of 90% rise in the prices, the allocated subsidy decreases by about 20%.